Peran Fasilitator Pendamping Dalam Pemberdayaan Ibu-Ibu Prasejahtera Produktif Untuk Meningkatkan Pendapatan UMKM Nasabah PT Bank BTPN Syariah Tbk - Adela Friska Putri; Nurhadi Nurhadi (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
The accompanying facilitator is a program from PT Bank BTN Syariah Tbk which aims to empower productive underprivileged mothers who are MSME actors by providing business assistance to customers. Micro, Small and Medium Enterprises are the biggest drivers of economic growth in Indonesia. However, in running their businesses, MSMEs often experience difficulties such as small scale businesses having difficulty accessing markets, limited capital, limited employees and limited knowledge. Where this happens to MSME actors, underprivileged women who are productive BTPN Syariah customers who are in rural areas who lack access to information to expand the market for products or services, due to the limited knowledge of MSME actors. The access to knowledge facilitator program aims to increase customers' entrepreneurial knowledge capacity so that they gain wider market access. In empowering productive underprivileged mothers, BTPN Syariah provides access to accompanying facilitators to customers with the aim of providing significant benefits and effects regarding increasing income, accessibility and customers gaining knowledge about entrepreneurship. It is hoped that this empowerment can improve the performance of MSME players so that they can develop business in businesses run by Bank BTPN Syariah customers.